Pengimplementasian Metode Forward Chaining Pada Perancangan Sistem Pakar Deteksi Penyakit Tidak Menular - Supit, Charenia; Rorimpandey, Gladly C (Innovative: Journal Of Social Science Research, 2023)
Non-communicable diseases (NCDs) refer to a group of diseases that do not spread between individuals. To address this issue, a tool known as an expert system is needed. An expert system is a computer program containing information from one or more human experts in a specific field. The method used in this expert system is forward chaining, a reasoning approach starting from facts to reach conclusions. Forward chaining is considered an inference strategy beginning with known facts, searching for new facts based on rules whose premises match existing facts. Testing this application demonstrates its effectiveness in diagnosing non-communicable diseases. Thus, an expert system using forward chaining can provide accurate and efficient solutions in handling NCDs.